Foreign Secretary Ernest Bevin and MI6's Covert Action Against France in North Africa, 1945–1948. Issue 3 (26th April 2022) - Zamir, Meir
Abstract: The principle of civilian control over the military and the secret services is essential for healthy democracies. That principle was challenged under the Labour government in Britain from 1945-1951, when the military and MI6 in the Middle East conducted their own parallel 'defence policy' using deception and misinformation, not only against their country's enemies, but against their own elected government. The outcome was a divided and confused foreign policy in a region that was considered vital to Britain's strategic interests. This research, which is based on sources from French, British, American and Israeli archives, as well as Syrian and other Arab documents, sheds light on the covert action of MI6 officers operating from their headquarters in Cairo with the backing of high-ranking officers in the Middle East Command, to subvert France's colonial rule in North Africa. Their clandestine activities contradicted the policy of Foreign Secretary Ernest Bevin, who sought to amend his country's relations with France after their clash in Syria in the summer of 1945, and integrate it in an anti-Soviet European alliance. The MI6 Arabists' covert action in French North Africa serves as a case study to re-evaluate Bevin's control of the organization, which was ostensibly accountable to him. The article questions Bevin's reputation as a powerful Foreign Secretary who dominated the Foreign Office, and raises doubts about his ability to oversee MI6's clandestine operations in the Middle East.